Sensitive Affimer and Antibody Based Impedimetric Label-Free Assays for C-Reactive Protein - Johnson, Anthony; Song, Qifeng; Ferrigno, Paul Ko; Bueno, Paulo Roberto [UNESP]; Davis, Jason J. (Amer Chemical Soc, 2012)
C-reactive protein (CRP) is an acute phase protein whose levels are increased in many disorders. Levels greater than 3 mu g/mL serum have hitherto been considered to indicate pathology, but there is increasing interest in assessments between 0.1 and 10 mu g/mL, which have been found to correlate with severity of risk for cardiovascular disease. We report herein the generation of both antibody and Affimer based impedance immunoassays for CRP that are substantially more sensitive than clinically utilized immunonephelometry and immunoturbidity assessments. Significant in this study is not only the use of a constrained peptide to detect a clinically important target but also that derived electrochemical impedance assays can be highly sensitive even with probes whose relatively weak (mu M) affinities are not amenable to target detection by surface plasmon resonance (SPR). Key to this finding is acknowledging that receptive surfaces of comparatively low initial steric bulk and charge transfer resistance are especially primed to be highly responsive to target binding in electroanalytical assays of this type.